Acceptability of donor breast milk banking, its use for feeding infants, and associated factors among mothers in eastern Ethiopia - Tilayie Feto Gelano; Yadeta Dessie Bacha; Nega Assefa; Aboma Motumma; Aklilu Abrham Roba; Yohanes Ayele; Fikirte Tsige (BMC, 2018)
Abstract Background The first priority for infant feeding is to encourage the use of infant's mother's breast milk, but when this is not possible, donated breast milk is the second best option. In developing countries, very few studies have been conducted on the acceptance of donor breast milk. Hence, this study was planned to discover the acceptability of donor breast milk banking, its use for feeding infants, and associated factors among mothers in eastern Ethiopia. Methods A mixed method study was conducted in eastern Ethiopia from December 2015 to February 2016. Data were collected through a pre-tested structured interview based questionnaire. A total of 1085 mothers participated in the survey and six focus group discussions were held with 33 mothers. Descriptive statistics have been used to report results from the survey and qualitative data were analyzed using the thematic data analysis approach. Results The study revealed that 119 (11%) of participants were willing to donate breast milk for banking and 165 (15.2%) of mothers were willing to use for feeding infants. The acceptance of donor milk banking was 5.8 times more likely among the mothers who had heard about donor milk banking previously (Adjusted Odds Ratio [AOR] 5.8; 95% Confidence Interval [CI] 3.1, 10.72), 4.2 times more likely among the mothers who heard about wet-nurses (AOR 4.2; 95% CI 2.5, 6.99) and 2 times more likely among mothers who had visited a neonatal intensive care unit (AOR 2; 95% CI 1.1, 3.73). Conclusions Generally, this study showed that the acceptance of breast milk donation for banking and its use for feeding infants was very low, due to lack of information and misconceptions about the safety of breast milk. Therefore, before initiation of any donor milk banking program awareness should be created about donor breast milk and its safety.